Género y educación en México - Parker, Susan Wendy; Pederzini Villarreal, Carla (El Colegio de México A.C., 2000)
This study examines the gender gap in education in Mexico, using the 1995 Population and Housing Survey as its main source of information. The size of the sample in this survey permits an analysis of the roles of rural and urban residence and poverty in educational achievement. It also contains detailed information on the number of years of study. The results confirm that the average number of years of schooling doubled over the forty years prior to the survey and that the gender gap has narrowed considerably. Despite the fact that girls' school attendance falls after the age of twelve, there are no differences between girls and boys in terms of average years of schooling. The study provides a number of explanations of this phenomenon and suggests a close link between educational achievement and wealth in Mexico.